The Application of Artificial Intelligence (AI) in Health Services within the Context of Positive Legality in Indonesia - Westiartika, Dhira Taramadia; Agustina, Ria; Anas, Kamal; Abdulhamid, Muhammad; Lidiawati, Meri; Prayuti, Yuyut (LEGAL BRIEF, 2025)
The quality and efficiency of healthcare services have changed significantly due to advances in digital technology and artificial intelligence (AI) in the medical field. However, these advances also present various legal, ethical, and social obstacles that require serious consideration. This study investigates the application of AI in the medical field from a progressive and responsive legal perspective. Using normative juridical methods and qualitatively analyzed secondary data. This study aims to establish adaptive regulations that can adapt to the changing nature of technology while protecting the integrity of medical services and patient rights. This study also shows the importance of integrating human and spiritual values ??into the application of medical technology to ensure that healthcare services are holistic and focused on patient welfare. The study findings suggest that the establishment of a safe, equitable, and sustainable digital health ecosystem depends on the collaboration of policymakers, medical personnel, technology experts, and the public. Therefore, to optimize the advantages of technology and reduce risks in the future healthcare sector, it is important to establish responsive and inclusive regulations based on lex specialist.